Pneumorrhachis with spontaneous pneumomediastinum in pediatric patients: An 11-year retrospective study in Southern Taiwan - Yu-Tang Chang; Chieh-Ni Kao; Yu-Ling Huang; Hung-Hsing Chiang; Jui-Ying Lee; Hsien-Pin Li; Po-Chih Chang; Shah-Hwa Chou; Yu-Wei Liu (Pediatrics and Neonatology)
Background: Although uncommon, available evidence suggests that pneumorrhachis (PR) with spontaneous pneumomediastinum (SPM) in adulthood is usually benign and self-limiting. This study aimed to review our experience and identify the risk factors of PR in pediatric patients with SPM. Methods: Between September 2007 and September 2017, SPM in patients aged ≤18 years was retrospectively reviewed and clinical features and outcomes between SPM patients with and without PR were analyzed. Results: In total, thirty consecutive occurrences of SPM in 29 patients were finally identified and classified into SPM (n = 24) and SPM plus PR (n = 6) groups. No significant differences in received interventional exams, prophylactic antibiotic administration or restriction of oral intake between the two groups were found. Both groups were treated with hospitalization predominantly; but the SPM plus PR group tended to have longer length of hospital stay (median 5.5 vs. 3 days, p = 0.08). PR was observed more frequently in patients with abnormal serum C-reactive protein (CRP) levels (>5 mg/L), identified predisposing factors, and those with more severe grade of SPM (p = 0.005, 0.001 and < 0.001, respectively). On multivariable regression analysis, the SPM plus PR group exhibited more predisposing factors than did the SPM group (coefficient: 0.514, standard error: 0.136, p < 0.001). All patients were successfully treated without morbidity and mortality. Conclusion: Although patients with pneumorrhachis retained a higher CRP level, more identified predisposing factors and prolonged inpatient care, conservative management without an extensive work-up would be an appropriate and favorable strategy in pediatrics with concurrent SPM and PR.